2016
DOI: 10.4067/s0718-58392016000400009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physiological and antioxidant activity of indica rice seedlings in response to mannitol-induced osmotic stress

Abstract: Morphological, physiological, and biochemical plant responses were studied in unstressed and stressed seedlings of indica rice (Oryza sativa L.) genotypes. The effect of NB medium supplemented with a 100 mM mannitol treatment, which induced drought stress conditions, was measured for relative growth rate, cell membrane stability, antioxidant enzyme activity (superoxide dismutase [SOD], catalase [CAT], and peroxidase [POD]), and total antioxidant capacity by DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2′-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 31 publications
1
27
0
2
Order By: Relevance
“…When plants are grown under adverse stress, free radicals or reactive oxygen species (ROS), such as H 2 O 2 , O 2 -• and HO• may accumulate. Under drought stress, plants have a limited capacity for C fixation, stomatal closure restricts the assimilation of CO 2 and leads to surplus electron flux to O 2 and overproduction of ROS (Chutipaijit 2016). When a certain threshold value is reached, ROS are toxic and capable of causing lipid peroxidation, oxidative damage to the DNA and cellular proteins and the leakage of intracellular electrolytes, ultimately damaging the structure and function of the cell membrane (Henricks and Nijkamp 2001;Siedlinski et al 2009;Gill and Tuteja 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When plants are grown under adverse stress, free radicals or reactive oxygen species (ROS), such as H 2 O 2 , O 2 -• and HO• may accumulate. Under drought stress, plants have a limited capacity for C fixation, stomatal closure restricts the assimilation of CO 2 and leads to surplus electron flux to O 2 and overproduction of ROS (Chutipaijit 2016). When a certain threshold value is reached, ROS are toxic and capable of causing lipid peroxidation, oxidative damage to the DNA and cellular proteins and the leakage of intracellular electrolytes, ultimately damaging the structure and function of the cell membrane (Henricks and Nijkamp 2001;Siedlinski et al 2009;Gill and Tuteja 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Production of radical ions under drought stress not only induces lipid peroxidation but also causes injury to membrane. Decrease in cell membrane stability in susceptible genotypes under drought is reported in contrast to tolerant genotypes (Chutipaijit, 2016).…”
Section: Ros Production Under Drought Stressmentioning
confidence: 99%
“…00,No. 0,201x Furthermore, it was revealed that the small increase in POD and CAT activity in drought-susceptible genotypes could decrease efficiency of rice plant cell to scavenge ROS (Chutipaijit, 2016). Drought tolerance in rice can be achieved by scavenging ROS using dehydrin proteins.…”
Section: Antioxidant Defense System and Rosmentioning
confidence: 99%
See 2 more Smart Citations